Lycium barbarum polysaccharides inhibit ischemia/reperfusion-induced myocardial injury via the Nrf2 antioxidant pathway. (2021) - Liu, Jin-Jun; Zhao, Gong-Xiao; He, Lei-Lei; Wang, Zheng; Zibrila, Abdoulaye Issotina; Niu, Bai-Chun; Gong, Hao-Yu; Xu, Jing-Ning; Soong, Lynn; Li, Chun-Fang; Lu, Yi
Graphical abstract: LBP attenuated myocardial ischemia/reperfusion injury by restoring redox status, ultimately improving cardiac function. CAT: catalase; GPX: glutathione peroxidase; HO1: heme oxygenase 1; IL-6: interleukin-6; I/R: ischemia/reperfusion; LBP: Lycium barbarum polysaccharides; Nrf2: nuclear factor erythroid 2-related factor 2; NQO1: NADPH dehydrogenase quinone 1; ROS: reactive oxygen species; SOD: superoxide dismutase; TNF-α: tumor necrosis factor α. Highlights: LBP attenuated myocardial oxidative stress and apoptosis induced by I/R. LBP improved cardiac function by reducing oxidative stress and apoptosis. LBP ameliorated myocardial I/R injury via activation the Nrf2 signal pathway. Abstract: Oxidative stress is considered to be one of main pathophysiological mechanisms in myocardial ischemia/reperfusion (I/R) injury. Lycium barbarum polysaccharides (LBP), the main ingredient of Lycium barbarum, have potential antioxidant activity. We aimed to investigate the effects of LBP on myocardial I/R injury and explore the underlying mechanisms. Myocardial I/R group was treated with or without LBP to evaluate oxidative stress markers and the role of Nrf2 signal pathway. Our results showed that I/R increased infarct size and the activities of creatine kinase (CK) and lactate dehydrogenase (LDH) when compared with control group. Meanwhile, the levels of reactive oxygen species (ROS), malondialdehyde (MDA), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) were enhanced and the activities of superoxide dismutase (SOD), glutathione peroxidase (GPX) and catalase (CAT) were decreased. These changes were associated with a significant increase in myocardial apoptosis, ultimately leading to cardiac dysfunction. LBP reduced infarct size (38.4 ± 2 % versus 19.4 ± 1.8 %, p < 0.05 ), CK and LDH activities and myocardial apoptotic index. Meanwhile, LBP suppressed the production of ROS and restored redox status. Additionally, LBP increased protein level of nuclear Nrf2 in vivo (2.1 ± 0.3 versus 3.8 ± 0.4, p < 0.05 ) and in vitro (1.9 ± 0.2 versus 3.8 ± 0.1, p < 0.05 ) and subsequently upregulated heme oxygenase 1 and NADPH dehydrogenase quinone 1 compared to I/R group. Interestingly, Nrf2 siRNA abolished the protective effects of LBP. LBP suppressed oxidative stress damage and attenuated cardiac dysfunction induced by I/R via activation of the Nrf2 antioxidant signal pathway.